THE SOCIAL SERVICE IN THE PROCESS OF COMMUNICATION IN CRITICAL SITUATIONS - Chagas Canuto, Ondina Maria; Santos de Castro Gadelha, Eliana; Brito dos Santos, Ruth (Cadernos ESP, 2021)
This article is an experience report that deals with the challenges of professional communication, in times of pandemic, in the face of the reality of critical situations, such as that referring to the communication of death. Its objectives are to reflect on the role of the social worker, as a member of the multiprofessional team, in a pandemic hospital context and the use of communication in professional practice, its weaknesses, tensions and to identify the skills necessary to carry out an ethical and human approach, in field of its competence. Of a qualitative nature, the present study contributes to the communication debate based on a critical reflection, articulating the theoretical-methodological, technical-operative and ethical-political dimensions of professional work, as well as, in the literature review, carrying out the documentary research and direct observation to analyze thematic categories on the meanings and uses of communication, inviting Social Work to build its own approach process.DESCRIPTORS: Communication; Pandemics; Social Work.
Keywords: Communication; Pandemics; Social Work